When a Theological Institution Becomes Ecumenical: A Focus on the Process and Experience - Hegertun, Terje (Dialog, 2016)
Det teologiske menighetsfakultet, or MF Norwegian School of Theology, has undergone an extensive development. From representing a strong Lutheran confessionalism, the new face of the faculty has changed to be more ecumenical in character. This article presents this story, gives insights into the historical process, and presents the current experiences of opening the school to non-Lutheran students and teachers. On the basis of this case study, the article reflects on ecumenical perspectives that could be constructive for the twenty-first century.